Synthesis and characterization of a doubly base-stabilized B3H6+ analogue - Schulenberg, Nikola; Wadepohl, Hubert; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2011)
The answer to an old question: A doubly base-stabilized B3H6+ analogue (see structure: B green, C gray, N blue, H light gray, H on C not shown) has been synthesized and completely characterized. Quantum-chemical calculations on a simplified model confirmed the presence of closed B-B-B three-center bonding and σ-aromatic character.
Die 3 und 6 im Titel sind tiefgestellt, das + ist hochgestellt
Gesehen am 27.10.2022